Innovative application of nested PCR for detection of Porphyromonas gingivalis in human highly calcified atherothrombotic plaques. Issue 1 (1st January 2020) - Brun, A.; Rangé, H.; Prouvost, B.; Mazighi, M.; Kapila, Y.; Bouchard, P.; Michel, J. B.
ABSTRACT: Atherothrombosis, leading to stroke and myocardial infarction, is responsible for most of the deaths in the world. An increased risk of atherothrombotic vascular events has been reported in patients with periodontitis. Periodontitis is a chronic multifactorial inflammatory disease, which involves a dysbiotic microbiota, and leads to a progressive destruction of the tooth-supporting apparatus. Transcient periodontal pathogen blood translocation, mainly bacteremia, has been associated with the severity of gingival inflammation. The identification of periodontal bacteria within atherothrombotic plaques is challenging and unpredictable. This review aims to summarize existing molecular technics for identifying periodontal microbiota in human atherothrombotic samples. A secondary objective is to describe a protocol for the identification of Porphyromonas gingivalis from highly calcified, atherothrombotic human samples that is based on our experience in translational cardiovascular research. Compared to direct real-time PCR, our protocol based on nested PCR has increased the detection of Porphyromonas gingivalis by 22.2% with good specificity.